2019
DOI: 10.1002/ecs2.2753
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing collaboration between ecologists and computer scientists: lessons learned and recommendations forward

Abstract: In the era of big data, ecologists are increasingly relying on computational approaches and tools to answer existing questions and pose new research questions. These include both software applications (e.g., simulation models, databases and machine learning algorithms) and hardware systems (e.g., wireless sensor networks, supercomputing, drones and satellites), motivating the need for greater collaboration between computer scientists and ecologists. Here, we outline some synergistic opportunities for scientist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Ecologists will then have to acquire or have access to good programming and/or mathematical skills and tools. While this might seem scary at first, we believe that there is one simple solution to this challenge: collaboration across disciplines (Carey et al, ). A stronger interaction between computer scientists and ecologists could also lead to new synergies and approaches in data classification and analyses, providing new insights for fundamental and applied research in ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists will then have to acquire or have access to good programming and/or mathematical skills and tools. While this might seem scary at first, we believe that there is one simple solution to this challenge: collaboration across disciplines (Carey et al, ). A stronger interaction between computer scientists and ecologists could also lead to new synergies and approaches in data classification and analyses, providing new insights for fundamental and applied research in ecology.…”
Section: Discussionmentioning
confidence: 99%
“…FreshWaterWatch has a global water quality database based on the contributions made by 8,000 + citizen scientists for more than 2,500 water bodies (freshwaterwatch.thewaterhub.org, 2019). Other projects, including Secchi Dip-In (Bigham Stephens et al 2015), Lake Observer (Carey et al 2019), Citclops (Busch et al 2016), Opal Water Survey (Rose et al 2016) and many more, could also inform this indicator. Given the potential of citizen science to support 6.3.2 and the large data gaps that exist, the custodian agency, UN Environment, can play a more active role by encouraging countries to apply citizen science to monitor water quality, and by providing guidelines for initiating and implementing citizen science projects at a local or national level.…”
Section: Indicator 632 Proportion Of Bodies Of Water With Good Ambimentioning
confidence: 99%
“…Our team found that computer science expertise was needed throughout the development and implementation of our forecasting system workflow, hardware, and software. Creating an iterative forecasting cycle running on a daily time step required close collaboration, trust, and a shared understanding of terminology and best practices from both freshwater ecology and computer science (following the recommendations of Carey et al 2019).…”
Section: Lesson 2: Cyberinfrastructure Is Not Trivialmentioning
confidence: 99%